"We are not lumpy to be treated like this ...": The Family Planning Program 1996-98 - Reyes, Esperanza (2000)
The consensus that has been reached in recent years in the execution of family planning programs around the world is to affirm that the effectiveness of their execution resides in an ethical attitude that privileges the rights of the person, a consensus that coincides with the demand of quality, focused on what the client requires.